Impact of Acadian Marine Plant Extract Powder (AMPEP) concentration in nutrient medium on the growth and lipid accumulation of Chlorella sp. Culture - Sarri, Jurmin; Erbil, Gökhun Çağatay; Elp, Mahmut (Ankara University Faculty of Agriculture, 2024)
Microalga of the genus Chlorella has developed a stable industry as dietary supplements for humans and animals based on their scientific and commercial interests. The growth of Chlorella sp. cultures has been enhanced by using a variety of nutrients to enhance pigmentation, lipid content, and growth. The use of Acadian Marine Plant Extract Powder (AMPEP) improves agricultural crops and macroalgae production, such as seaweeds. However, AMPEP has not yet been studied as a means of producing microalgae. Therefore, this study investigates microalgae production in a nutrient medium containing AMPEP. Three concentrations of AMPEP were prepared: group A (125 mg L-1 AMPEP), group B (625 mg L-1 AMPEP), and group C (0 mg L-1 AMPEP) as control. Experiments were conducted for each group for 21 days in triplicate. Results revealed that lower AMPEP (125 mg L-1) concentration added to the nutrient medium provides higher cell densities in Chlorella sp. culture. 125 mg L-1 AMPEP in a nutrient medium reached the highest cell density of 1.28 fold cell mL-1 than the control group. Additionally, the dry weight of groups A, B, and C were calculated as 2.57 ± 0.12 g L-1, 1.37 ± 0.06 g L-1, and 1.58 ± 0.16 g L-1, respectively. The cell size of groups A, B, and C were 4.80 ± 1.32 μm, 5.20 ± 1.87 μm, and 3.80 ± 0.79 μm, respectively. Moreover, the highest level of lipid accumulation of Chlorella sp. culture was achieved by group B with a lipid content of 10.44 ± 1.28 %, followed by group A with a lipid content of 8.55 ± 0.80 %, which was higher than the control group (group C) with a lipid content of 7.04 ± 0.93 %. Hence, the present study shows that AMPEP used in microalgae production may improve growth and lipid accumulation.
Keywords: lipids; Sucul Kültür; chlorella sp.; growth; pigments; Agriculture (General); AMPEP; Chlorella sp.; growth; pigments; lipids; Aquaculture; ampep; S1-972